If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6y + -12 + 2y = 28 Reorder the terms: -12 + -6y + 2y = 28 Combine like terms: -6y + 2y = -4y -12 + -4y = 28 Solving -12 + -4y = 28 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + -4y = 28 + 12 Combine like terms: -12 + 12 = 0 0 + -4y = 28 + 12 -4y = 28 + 12 Combine like terms: 28 + 12 = 40 -4y = 40 Divide each side by '-4'. y = -10 Simplifying y = -10
| 1/4x+1/2x=-1/8 | | y=-14/3(12) | | 4n+8=-24 | | -4/5-1/3w=-1/2 | | y=28/3/-1/2 | | 2(8+f)=22 | | 7(7x-77)=98 | | 100(b-3)=450-50b | | X=.8x+4 | | -7x-4(x+10)=-139 | | 2.33333333333= | | -3g-g=24 | | 7(h-1)=3(h+1/3) | | r/6=14 | | 5x+3y=x | | 24a-12a=24 | | 2r+200=2000 | | y=-25/5(12) | | 16x^2+40x+15=0 | | 1/y-6=-11 | | X/5-3=4 | | -20=-6p | | -8/15a=9/10 | | 2x^5-3x^4-12x^3+12x^2-14x+12=0 | | -2=2y+4 | | -6t-p+4p-5t= | | 40-2y=6y | | 7y+7y+3y+5y-3y-5y+8y-y=28 | | 36x+33=465 | | 9x+5x=45 | | x-9(-9/14)=5/7 | | -x+6-x=2(x+3) |